2010
DOI: 10.3747/pdi.2008.00277
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Reasons for Peritoneal Dialysis Technique Failure and Mortality

Abstract: ♦♦ ♦♦ ♦ Background: Peritoneal dialysis (PD) technique failure is high compared to hemodialysis (HD). There is a lack of data on the impact of duration of PD treatment on technique survival and on whether there is a difference in risk factors with respect to early and late failure. The aim of this study was to clarify these issues by performing a timedependent analysis of PD technique and patient survival in a large cohort of incident PD patients. ♦♦ ♦♦ ♦ Methods: We analyzed 709 incident PD patients participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
153
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 22 publications
14
153
1
8
Order By: Relevance
“…That finding might point to some selection bias at the start and during dialysis: patients with a contraindication for hemodialysis, mainly of a cardiologic nature, typically start with PD (27). However, reasons for withdrawal from PD did not vary during the years on PD and resembled those recorded in another study (28). As judged from those findings, patients with different numbers of available SPAs were quite similar at baseline, justifying our approach of analyzing the time course in this group.…”
Section: Discussionmentioning
confidence: 56%
“…That finding might point to some selection bias at the start and during dialysis: patients with a contraindication for hemodialysis, mainly of a cardiologic nature, typically start with PD (27). However, reasons for withdrawal from PD did not vary during the years on PD and resembled those recorded in another study (28). As judged from those findings, patients with different numbers of available SPAs were quite similar at baseline, justifying our approach of analyzing the time course in this group.…”
Section: Discussionmentioning
confidence: 56%
“…Regarding the protective effect of older age on technique failure, information in the literature is controversial (29)(30). The greater risk of technique failure in elderly patients could be attributed to reasons such as an inability to perform PD because of cognitive or mechanical reasons; however, similar to the present results Lim et al (25), in a large Australia and New Zealand cohort, reported that compared to younger patients, elderly patients presented a higher risk of peritonitis-related mortality, but a lower risk of technique failure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the attention given to issues such as adequacy of clearances, ultrafiltration failure, and lack of home support, peritonitis remains the leading cause of technique failure in most peritoneal dialysis (PD) centers (1,2). Furthermore, recent audits from a number of regions suggest that peritonitis rates in unselected centers are often higher than those reported from motivated centers of excellence.…”
mentioning
confidence: 92%
“…Intriguingly, one randomized trial showed a decline in gram-negative non-Pseudomonas peritonitis, which had previously been thought not usually to enter the peritoneal cavity via the exit site and tunnel (13). Despite these encouraging studies, uptake of these strategies has not been universal, and peritonitis rates do not appear to have fallen in the same way that they did when Y sets were introduced (1,2,10). This raises some questions.…”
mentioning
confidence: 99%